Poloxamer 407/TPGS mixed micelles for delivery of gambogic acid to breast and multidrug-resistant cancer - Saxena, Vipin (Dove Medical Press, 2012)
BACKGROUND: Delivery of a high concentration of anticancer drugs specifically to cancer cells remains the biggest challenge for the treatment of multidrug-resistant cancer. Poloxamers and D-α-Tocopheryl polyethylene glycol 1000 succinate (TPGS) are known inhibitors of P-glycoprotein (P-gp). Mixed micelles prepared from Poloxamer 407 and TPGS may increase the therapeutic efficacy of the drug by delivering high concentrations inside the cells and inhibiting P-gp. Gambogic acid (GA) is a naturally derived novel anticancer agent, but poor solubility and toxic side effects limit its use. In this study, we have developed Poloxamer 407 and TPGS mixed micelle-encapsulating GA for the treatment of breast and multidrug-resistant cancer. METHODS: GA-loaded Poloxamer 407/TPGS mixed micelles were prepared using a thin film hydration method, and their physicochemical properties were characterized. Cellular accumulation and cytotoxicity of the GA-loaded Poloxamer 407/TPGS mixed micelles were studied in breast cancer cells, MCF-7 cells, and multidrug-resistant NCI/ADR-RES cells. RESULTS: The diameter of GA-loaded Poloxamer 407/TPGS mixed micelles was about 17.4 ± 0.5 nm and the zeta potential −13.57 mV. The entrapment efficiency of GA was 93.1% ± 0.5% and drug loading was about 9.38% ± 0.29%. Differential scanning calorimetry and X-ray powder diffraction studies confirmed that GA is encapsulated by the polymers. The in vitro release studies showed that mixed micelles sustained the release of GA for more than 4 days. Results from cellular uptake studies indicated that GA-loaded Poloxamer 407/TPGS mixed micelles had increased cellular uptake of GA in NCI/ADR-RES cells. Cytotoxicity of GA-loaded Poloxamer 407/TPGS mixed micelles was found to be 2.9 times higher in multidrug-resistant NCI/ADR-RES cells, and 1.6 times higher in MCF-7 cells, as compared with unencapsulated GA. CONCLUSION: This study suggests that Poloxamer 407/TPGS mixed micelles can be used as a delivery system for GA to treat breast and multidrug-resistant cancer.